Pengaruh Hypnobirthing terhadap Tingkat Kecemasan pada Ibu Hamil di Wilayah Kerja Puskesmas Siatas Barita Tahun 2020 - Dimpu Rismawaty Nainggolan; Riance Mardiana Ujung; Paruhum Tiruon Ritonga (EMBRIO: Jurnal Kebidanan, 2021)
Psychological changes in pregnant women include experiencing anxiety which can increase stress and severe stress during childbirth and can cause abnormalities. Childbirth history that is not good can affect the health of the mother and fetus. This situation can cause the muscles in the body to become stiff, especially the perineal muscles to become stiff and hard, making it difficult to adapt to the development and delivery process, unbalanced emotions and even increased and difficult to control. Hypnobirthing is a way that pregnant women do by doing relaxation because it can increase the hormone endorphins that can relieve pain in the body. This study aims to analyze the effect of Hypnobirthing on the anxiety of pregnant women before and after treatment and prove whether there is an impact of hypnobirthing to reduce maternal anxiety. pregnant in the working area of ​​the Siatas Barita Health Center. This type of research uses treatment before giving a pre-test to the group. Then the researchers did a hypnobirthing simulation. Next, a post-test was carried out. The population is mothers with gestational age above 12 weeks. Methods Bivariate analysis uses the Wilcoxon test calculation and then the results are described. Based on the calculation results indicate that there is a relevant impact of hypnobirthing on reducing anxiety in respondents (p = 0.016). Before receiving Hypnobirthing treatment, the anxiety level of pregnant women was higher than those who had received treatment.